Studi Analisis Koordinasi Over Current Relay (OCR) dan Ground Fault Relay (GFR) pada Recloser di Saluran Penyulang Penebel - Agung Budhi Udiana, I Dewa Gde; Dyana Arjana, I G; Indra Partha, Tjok Gede (Majalah Ilmiah Teknologi Elektro; Vol 16 No 2 (2017): (May - Agustus) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2017.v16i02p07, 2017)
Short circuit causing over current problem and can might causing interference of the equipment performance such as distribution transformers also causing widespread disruption occurred. In resolving such interference is required as protection system on the distribution system. Seeing all above is needed coordination between the supporting component of the protection system which is consisted of Over Current Relay (OCR) and Ground Fault Relay (GFR). The research was conducted at PT. PLN (Persero) South Bali Area Network, INDONESIA on recloser in the feeder line of Penebel. OCR setting between the Relay feeder of Penebel, Recloser Celagi, Recloser Bakisan, and Recloser Benana still less selective, with time value coordination between average security was still less than 0,2 second. Then OCR setting and GFR relay feeder of Penebel, Recloser Celagi, Recloser Bakisan, and Recloser Benana was recommended for re-setting in order to minimize disruption and electric power distribution system to be reliable.
Keywords: Over Current Relay (OCR), Ground Fault Relay (GFR), Recloser, Protection, Short Circuit